Kontestasi Peribadatan Antara Kaum Tua dan Muda Muslim Pasca Pandemi - Fernando, Henky; Larasati, Yuniar Galuh (Institut Agama Islam Negeri Fattahul Muluk Papua, 2023)
Muslim worship activities after the pandemic have given rise to various kinds of contestation in practice and meaning. Studies that have discussed this phenomenon only focus on the adaptation and recovery of socio-religious activities, so they have not comprehensively discussed the contestation of Muslim worship after the pandemic. This study focuses on the contestation of worship between young and old Muslims after the pandemic. This study uses a descriptive qualitative approach to many Muslims who actively practice the five daily prayers in congregation at the mosque. These Muslims were interviewed intensively to obtain data on their post-pandemic worship intensity, activities, and commitment. The findings in this study show that not only can worship activities no longer return to normal as practiced before the emergence of the COVID-19 pandemic, but it is also not uncommon for Muslim worship practices, attitudes, and commitments to become more contestative after the pandemic. This study also recommends the importance of explaining and reflecting on the post-pandemic worship activities of Muslims in a more macro and comparative community context.